2019
DOI: 10.1002/jmri.26928
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biochemical recurrence in prostate cancer patients who underwent prostatectomy using routine clinical prostate multiparametric MRI and decipher genomic score

Abstract: Background Biochemical recurrence (BCR) affects a significant proportion of patients who undergo robotic‐assisted laparoscopic prostatectomy (RALP). Purpose To evaluate the performance of a routine clinical prostate multiparametric magnetic resonance imaging (mpMRI) and Decipher genomic classifier score for prediction of biochemical recurrence in patients who underwent RALP. Study Type Retrospective cohort study. Subjects Ninety‐one patients who underwent RALP performed by a single surgeon, had mpMRI before RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
(58 reference statements)
2
26
0
Order By: Relevance
“…First, implicit bias may exist due to the retrospective nature of the study; however, the multi-institutional validation suggests the robustness of RadClip. In addition, even though 198 patients were included in this study, this number is actually larger compared to other recent related studies [17,18,40]. However, we acknowledge that prior to clinical deployment, the approach needs additional retrospective and potentially prospective clinical trial validation in the future to further confirm the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…First, implicit bias may exist due to the retrospective nature of the study; however, the multi-institutional validation suggests the robustness of RadClip. In addition, even though 198 patients were included in this study, this number is actually larger compared to other recent related studies [17,18,40]. However, we acknowledge that prior to clinical deployment, the approach needs additional retrospective and potentially prospective clinical trial validation in the future to further confirm the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 81%
“…al. illustrated that combing clinicopathologic parameters with mpMRI was comparable in prediction of BCR as a combination of Decipher and clinicopathologic parameters [40]. This study was however limited in its sample size, single institutional design and the fact that PI-RADS is known to be subject to interreader variability [41].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this retrospective multi-institutional study, we investigated and compared the potential of CAPRA score and predictive models in predicting the BCR risk after RP using routine variables. We note that the CAPRA score is a commonly used prediction model for the occurrence of biochemical and clinical recurrences developed from the CaPSURE registry ( 5 ) with many studies providing external validation with other cohorts ( 7 , 19 ). In this study, we found that CAPRA score showed a c-index of 0.63 to predict the 3-year-BCR rates with the prognostic variables obviously differing from those of the original CaPSURE cohort.…”
Section: Discussionmentioning
confidence: 99%